Gambaran Imunohistokimia pada Pasien Infeksi Herpes Simplex Virus 1 dengan Karsinoma Tiroid: Sebuah Serial Kasus - Putri Jati Utami; Prasetyadi Mawardi; Utiya Nur Laili; Larisa Sabrina Rahadiyanti; Triasari Oltavriana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Thyroid carcinoma is one of the most common endocrine cancers with a multi-factorial etiology. The role of HSV-1 in the pathogenesis of thyroid cancer remains an area of ongoing investigation. HSV-1 may be present in thyroid tissue raising questions about its potential role in thyroid carcinogenesis. The first case involves a 65-year-old male diagnosed with thyroid carcinoma, presenting with a history of oral discomfort and pain two weeks before evaluation. The second case is a 73-year-old male, also diagnosed with thyroid carcinoma with no history of herpes simplex virus (HSV). Both patients underwent thyroidectomy, and histopathological examination confirmed the presence of papillary carcinoma in thyroid tissue. Immunohistochemical analysis further identified HSV-1 in both cases. A study has reported a higher frequency of HSV DNA detection in thyroid carcinoma, with a significant correlation between oncogenic mutations and HSV presence. The upregulation of nectin-1 expression in thyroid carcinoma facilitates HSV occurrence, thereby increasing the susceptibility of cancer cells to viral infection. Moreover, thyroid hormone levels may play a role in HSV reactivation, highlighting the intricate interplay between thyroid function, viral activity, and cancer progression. Histopathological examination, including immunohistochemical (IHC) staining, identified HSV 1 in two patients diagnosed with thyroid carcinoma. These findings underscore the need for further research involving a larger cohort to elucidate the potential role of HSV in thyroid carcinogenesis.